Study on mechanical behavior of rockfall impacts on a shed slab based on experiment and SPH–FEM coupled method. (October 2021) - Zhong, Hanqing; Lyu, Liang; Yu, Zhixiang; Liu, Chun
Abstract: The mechanical behavior of rockfall impacts on shed slabs was studied in three aspects: the rockfall impact force, the inertia effect coefficient, and the structural damage evaluation. A test model composed of a concrete slab and a cushion layer was constructed. Nine batches of impact experiments with energies ranging from 50 to 250 kJ were conducted. The dynamic impact model was established using LS-DYNA to analyze the dynamic impact response characteristics and inertia effect based on the SPH–FEM coupled method. Moreover, random sample expansions were calculated, and methods for assessing the impact force and inertia effect coefficient were proposed. In addition, the applicability of the proposed equation was verified by comparing the calculated results with relevant published experimental data and the Japanese calculation method of impact force. Furthermore, the velocity and mass of the rockfall were selected as the main control variables for damage assessment. A damage assessment index based on punching bearing capacity was established, and the level of damage was classified. Additionally, the influence of the parameters of the concrete slab and cushion layer thickness on damage assessment was analyzed. The impact resistances of the Ultra-High Performance Concrete (UHPC) and normal concrete slab were compared. The results demonstrated that the effect of impact force and the concurrent impact-induced inertia effect should be considered in structural designs. The larger the mass rockfall, the greater the damage sustained by the slab under the same impact energy. The compressive strength of concrete and the yield strength of steel have the greatest and least influence on the damage degree, respectively. A 90 cm-thick sand cushion on a slab increases the impact resistance of the slab by 25%–30%, compared with a 60 cm-thick sand cushion layer. Moreover, it was found that the UHPC concrete slab has good impact resistance, which is approximately twice that of the C40 concrete slab. One of the highlights in this paper is that the SPH–FEM coupled method is proposed to reproduce the physical phenomenon of sand pit-forming. Compared with FEM, SPH–FEM generates a simulated value that is closer to the experimental value.